1996
DOI: 10.1007/bf02507101
|View full text |Cite
|
Sign up to set email alerts
|

Binding of autoantibodies is not restricted to desmosomes in pemphigus vulgaris:

Abstract: Pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are autoimmune blistering diseases characterized by a loss of cell-cell adhesion and by autoantibodies directed against epidermal cadherins. PF antigen has been established as desmoglein I which is located strictly on the desmosome, whereas the precise ultrastructural localization of PV antigen remains unclear and controversial to date. To further investigate this question, we compared the location of immune deposits in 14 patients with PV and 10 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In fact, although Dsg molecules are indeed predominantly localized to desmosomes [168], binding of PV IgG extends well beyond the desmosomes decorating the entire surface of keratinocytes [169]. As already mentioned, the Dsg-Fc-IgG constructs were found to be not specific for Dsg 1 or 3 antibodies [18,36].…”
Section: Molecular Mechanisms Of Keratinocyte Detachment In Pemphigusmentioning
confidence: 99%
“…In fact, although Dsg molecules are indeed predominantly localized to desmosomes [168], binding of PV IgG extends well beyond the desmosomes decorating the entire surface of keratinocytes [169]. As already mentioned, the Dsg-Fc-IgG constructs were found to be not specific for Dsg 1 or 3 antibodies [18,36].…”
Section: Molecular Mechanisms Of Keratinocyte Detachment In Pemphigusmentioning
confidence: 99%
“…Although it has been postulated that binding of pemphigus IgGs to the desmosomal cadherins Dsg 1 and 3 interferes with cell-cell adhesion due to steric hindrance (42), binding of pemphigus autoantibodies to KC is not restricted to the desmosomal areas (43,44). Acantholysis in both skin and organ cultures treated with pemphigus IgGs starts from intracellular events such as retraction of tonofilaments, followed by widening of the intercellular space at the non-desmosomal areas with desmosomes remaining intact (45)(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…One of the earliest indications that alternative mechanisms may drive pathogenesis was the observation that IgG from PF patients could induce disease in mice without interfering with trans-adhesion of Dsg1 ( 27 ). It was noted in multiple studies that PVIgG was seen to bind extra-desmosomal spaces on the surface of keratinocytes, allowing for the possibility that binding of autoAbs outside of desmosomes may affect disease ( 3 , 28 ). It was also shown that PVIgG binding induced cytoskeletal changes and the retraction of keratin intermediate filaments before any visible changes in desmosomes ( 29 33 ).…”
Section: Introductionmentioning
confidence: 99%